DEVELOPMENT OF A DEVICE FOR AUTOMATIC GAIN SELECTION OF A MEASURING AMPLIFIER USING A FOLLOWING TYPE ANALOGUE-DIGITAL CONVERTER - Bazarov Makhammatyakub; Abidova Gulmira Shuxratovna; Qurbonov Islom Baxtiyorovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the increase in the efficiency of the device for automatic selection of the gain of the measuring amplifier using an analog-to-digital converter of the servo type. A block diagram of the developed analog-to-digital converter of the tracking type is presented, which, by its principle of operation and complexity, is an order of magnitude simpler than the others.